Knowledge, attitudes, and practices of physicians regarding multidisciplinary treatment of obstructive sleep apnea: a cross-sectional study - Peili Shen (Scientific Reports)
Abstract To investigate physicians’ knowledge, attitudes, and practices (KAP) regarding the multidisciplinary treatment of Obstructive Sleep Apnea (OSA). A multicenter cross-sectional study was conducted in May 2024, enrolling physicians from southwestern China. The study collected demographic data and assessed KAP through self-administered questionnaires, with the respiratory and otolaryngology departments defined as relevant departments. A total of 329 valid questionnaires were collected. Of these respondents, 173 (52.6%) were female, and 114 (34.7%) had participated in multidisciplinary OSA-related training. The mean scores for knowledge and attitudes were 24.61 ± 8.27 (possible range: 0–34) and 39.99 ± 4.34 (possible range: 10–50), respectively. Practice scores of the physicians in departments directly and indirectly involved in OSA treatment averaged 24.28 ± 4.70 and 21.28 ± 4.24 (possible range: 6–30), respectively. Structural equation modeling results indicated that in departments directly related to OSA, knowledge had a significant positive effect on both attitudes (β = 5.53, P < 0.001) and practices (β = 5.8, P < 0.001). For departments indirectly related to OSA, knowledge had a significant positive effect on attitudes (β = 5.41, P < 0.001). Physicians showed adequate knowledge and attitudes toward OSA treatment; targeted education is recommended to enhance consistency in practices across departments.